Effects of salt stress on plant and rhizosphere bacterial communities, interaction patterns, and functions - Fu, Maoxing; Liu, Liying; Fu, Bingzhe; Hou, Meiling; Xiao, Yanzi; Liu, Yinghao; Sa, Duowen; Lu, Qiang (Frontiers in Plant Science, 2025)
Introduction Salt stress significantly affects plant growth, and Na+ has gained attention for its potential to enhance plant adaptability to saline conditions. However, the interactions between Na+, plants, and rhizosphere bacterial communities remain unclear, hindering a deeper understanding of how Na+ contributes to plant resilience under salt stress. Methods This study aimed to investigate the mechanisms through which Na+ promotes alfalfa's adaptation to salt stress by modifying rhizosphere bacterial communities. We examined the metabolic activity and community composition of both plant and rhizosphere bacteria under Na+ treatment. Results and discussion Our results revealed significant changes in the metabolism and community composition of both plant and rhizosphere bacteria following Na+ addition. Na+ not only promoted the growth of rhizosphere bacteria but also induced shifts in the plant-associated bacterial community, increasing the abundance of bacterial species linked to alfalfa's resistance to salt stress. Furthermore, the chemical characteristics of alfalfa were strongly correlated with the composition and network complexity of both plant and rhizosphere bacterial communities. These interactions suggest that Na+ plays a crucial role in enhancing alfalfa’s adaptability to salt stress by fostering beneficial bacterial communities in the rhizosphere. This finding highlights the potential of leveraging Na+ interactions with plant-microbe systems to improve crop resilience and productivity in saline agricultural environments.